Equity in health care delivery and finance - John Roemer (University of California, Department of Economics, 1999)
Much has happened in the theory of distributive justice during the last 30 years, in the period, roughly, since Rawls published his magisterial work1. As occurs in most fields following a great contribution, that work has been subjected to critique, amended and ramified, so that what Rawls proposed now appears as an early ancestor of contemporary theories of distributive justice, or equity. In this paper, I locate what I think is the main trend in this developing theory, and then to try to apply the theory to the issue of health.
Keywords: 330